Early oral intake through meticulous chewing after esophagectomy - Wong, Ian; Law, Simon (Journal of Thoracic Disease; Vol 10, Supplement 17 (June 20, 2018): Journal of Thoracic Disease, 2018)
Enhanced recovery after surgery (ERAS) has gained popularity in surgery, having the potential to reduce morbidity rates, shorten hospital stay, and lessen the cost. Esophagectomy has high morbidities among general surgical operations and is ideal for ERAS to make an impact. Among the various components in the multidisciplinary ERAS management program, nutritional support and early oral feeding are very relevant to esophageal surgery.